Impacts of acetone on the spray combustion of Acetone–Butanol–Ethanol (ABE)-Diesel blends under low ambient temperature. (15th February 2015) - Wu, Han; Nithyanandan, Karthik; Zhou, Nan; Lee, Timothy H.; Lee, Chia-fon F.; Zhang, Chunhua
Highlights: Acetone–Butanol–Ethanol (ABE) with various component ratios were blended with diesel. ABE with typical ratio will increase ignition delay at lower ambient temperature. Extra acetone in ABE–Diesel blends will improve the combustion characteristics. ABE–Diesel blends could reduce natural luminosity intensity at various conditions. Abstract: Acetone–Butanol–Ethanol (ABE), an intermediate product in the ABE fermentation process for producing bio-butanol, is considered a promising alternative fuel because it not only preserves the advantages of oxygenated fuels which present lower soot emissions compared to diesel, but also lowers the cost of fuel recovery for individual component during fermentation. The advantageous characteristics of ABE–Diesel include higher oxygen content which promotes soot oxidation; longer ignition delay and flame lift-off length allowing more air entrainment upstream of the spray jet thus providing better air–fuel mixing. With the development of advanced ABE fermentation technology, the volumetric percentage of acetone, butanol and ethanol in the bio-solvents can be precisely controlled. In this respect, it is desirable to estimate the performance of different ABE blends to determine the best blend and optimize the production process accordingly. In this paper, ABE fuels with different component volumetric ratio (A:B:E of 6:3:1; 3:6:1; 0:10:0), were blended with 80% vol. diesel and injected into a constant volume chamber. The combustion characteristics of these blends were experimentally investigated under LTC conditions (ambient temperature of 800 K with varying ambient oxygen content). Time-resolved broadband luminosities from the combustion process were captured by a high speed camera and flame lift-off lengths were also acquired. The impacts of acetone and butanol content on the combustion characteristics of the blends were addressed in detail. ABE20(6:3:1) displayed combustion characteristics very similar to those of pure diesel, displaying a much shorter ignition delay than that of the other ABE–Diesel blends due to a high fraction of acetone. At the same time, ABE20(6:3:1) presented a much lower natural flame luminosity (lower soot formation) compared to diesel, owing to its shorter combustion duration and stronger premixed combustion.